Studies on renal safety and preventive analgesic efficacy of tramadol and parecoxib in dogs : thesis in fulfilment of the degree of Doctor of Philosophy in Veterinary Clinical Science, Institute of Veterinary Animal and Biomedical Sciences, College of Sciences, Massey University, Palmerston North, New Zealand - Kongara, Kavitha (Massey University, 2008)
Ovariohysterectomy and castration are common surgical procedures in small animal practice that can result in clinically significant postoperative pain. One way of controlling postoperative pain is administration of a single analgesic or a combination of different classes of analgesics prior to the onset of noxious stimuli. A constraint to the perioperative use of traditional opioids and non-steroidal anti-inflammatory drugs (NSAIDs) is their undesirable side effects. In this series of experiments, the preventive (pre-emptive) analgesic efficacy of two popular human analgesics, tramadol (an ?atypical? opioid) and parecoxib (a NSAID with selective COX-2 inhibition) was evaluated in dogs. Initially, the efficacy and renal safety of parecoxib, tramadol and a combination of parecoxib, tramadol and pindolol (a -adrenoceptor blocker and 5-HT1A/1B antagonist) were screened in anaesthetised healthy dogs. These analgesics increased the dogs? nociceptive threshold to mechanical stimuli, without causing significant alterations in the dogs? glomerular filtration rate (GFR) estimated by plasma iohexol clearance. Subsequently, the efficacy of tramadol was compared with morphine, in dogs undergoing ovariohysterectomy or castration. The Glasgow composite measure pain scale-short form score (CMPS-SF) and changes in intraoperative electroencephalogram (EEG) responses were used to assess the efficacy of analgesics. Of the three treatment groups (preoperative morphine, 0.5 mg kg-1; preoperative tramadol, 3 mg kg-1; a ?combination? of preoperative low-dose morphine, 0.1 mg kg-1, and postoperative tramadol 3 mg kg-1), dogs given the ?combination? had significantly lower pain scores after ovariohysterectomy. In castrated dogs, preoperative tramadol (3 mg kg-1) and morphine (0.5 mg kg-1) were tested and no significant difference in the CMPS-SF score were observed between them. Changes in EEG variables were not specific between the treatment groups in ovariohysterectomised dogs. Finally, the efficacy of test drugs was evaluated against acute noxious electrical stimulation in anaesthetised dogs, using EEG. Median frequency of the EEG, a reliable indicator of nociception, increased significantly in tramadol and parecoxib groups, compared to morphine, after electrical stimulation. These studies demonstrated that tramadol and parecoxib can produce analgesia in dogs with insignificant side effects. The efficacy of tramadol appears to vary with the type of noxious stimulus. A complete prevention of noxious input by administration of analgesics pre- and post-operatively could have important clinical applications.
Keywords: Analgesics; Anaesthesia; Pain relief; Dog surgery; Pain in animals; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300502 Anaesthesiology and intensive care